Vaporization, Diffusion and Combustion of Laser-Induced Individual Magnesium Microparticles in Inert and Oxidizing Atmospheres - Fan Yang (MDPI AG, 2021)
Although the gas phase combustion of metallic magnesium (Mg) has been extensively studied, the vaporization and diffusive combustion behaviors of Mg have not been well characterized. This paper proposes an investigation of the vaporization, diffusion, and combustion characteristics of individual Mg microparticles in inert and oxidizing gases by a self-built experimental setup based on laser-induced heating and microscopic high-speed cinematography. Characteristic parameters like vaporization and diffusion coefficients, diffusion ratios, flame propagation rates, etc., were obtained at high spatiotemporal resolutions (μm and tens of μs), and their differences in inert gases (argon, nitrogen) and in oxidizing gases (air, pure oxygen) were comparatively analyzed. More importantly, for the core–shell structure, during vaporization, a shock wave effect on the cracking of the porous magnesium oxide thin film shell-covered Mg core was first experimentally revealed in inert gases. In air, the combustion flame stood over the Mg microparticles, and the heterogeneous combustion reaction was controlled by the diffusion rate of oxygen in air. While in pure O2, the vapor-phase stand-off flame surrounded the Mg microparticles, and the reaction was dominated by the diffusion rate of Mg vapor. The diffusion coefficients of the Mg vapor in oxidizing gases are 1~2 orders of magnitude higher than those in inert gases. However, the diffusive ratios of condensed combustion residues in oxidizing gases are ~1/2 of those in inert gases. The morphology and the constituent contents analysis showed that argon would not dissolve into liquid Mg, while nitrogen would significantly dissolve into liquid Mg. In oxidizing gases of air or pure O2, Mg microparticles in normal pressure completely burned due to laser-induced heating.